Menyelami Filosofi Lonto Leok: Persatuan dan Konsensus dalam Budaya Manggarai - Sili, Adrianus Musu; Iswandi, Ferdinandus; Nefrindo, Oktavianus; Mulyatno, Carolus Borromeus (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Lonto Léok, a tradition from Manggarai, Indonesia, reflects a significant transformation in the context of unity and communal decisions. Originating from inter-tribal conflicts, this tradition has evolved into a symbol of family unity. In Lonto Léok, formal interaction mechanisms are led by a leader known as "Tu'a Golo," who serves as a facilitator and guides the deliberation process. There are three main stages in Lonto Léok: "caca" (unpack), "cica" (discuss), and "congko" (finalize), reflecting an intensive deliberation process to reach collective agreements. This research aims to elucidate the history, meaning, and mechanisms of Lonto Leok in Manggarai culture while highlighting issues that still need to be addressed. The author adopts a qualitative method based on literature review, interviews, and the author's direct experiences as data sources. The research findings reveal that the shift in the meaning of Lonto Léok from battle to family unity demonstrates cultural adaptability in the face of social change. Lonto Léok represents how the Manggarai community manages conflicts and achieves consensus through deliberation and agreement.AbstrakLonto Léok, sebuah tradisi dari Manggarai, Indonesia, mencerminkan transformasi signifikan dalam konteks persatuan dan keputusan komunal. Tradisi ini, yang berasal dari masa konflik antarsuku, kini menjadi simbol persatuan keluarga. Dalam Lonto Léok, mekanisme interaksi formal dipimpin oleh seorang pemimpin yang dikenal sebagai "Tu'a Golo," yang bertugas sebagai fasilitator dan memandu proses musyawarah. Terdapat tiga tahapan utama dalam Lonto Léok: "caca" (bongkar), "cica" (bahas), dan "congko" (rampung), yang mencerminkan proses musyawarah intens untuk mencapai kesepakatan kolektif.  Penelitian ini bertujuan untuk menjelaskan sejarah, makna, dan mekanisme Lonto Leok dalam budaya Manggarai sambil menyoroti masalah yang masih perlu diatasi. Penulis mengadopsi metode kualitatif dengan berlandaskan pada studi pustaka, wawancara, dan pengalaman langsung penulis sebagai sumber data. Hasil penelitiannya adalah pergeseran makna Lonto Léok dari pertempuran menjadi persatuan keluarga menunjukkan adaptabilitas budaya dalam menghadapi perubahan sosial. Lonto Léok adalah cara masyarakat Manggarai mengelola konflik dan mencapai kesepakatan melalui musyawarah dan konsensus.